Novel Hierarchically Structured Nanocomposites for Biomedical Applications - Liu, Tingting (Curtin University, 2017)
It is a great challenge to design hierarchically structured nanocomposites with multicomponents for biomedical applications. Here, we demonstrate the synthesis of a library of biocompatible nanocomposites, possessing diverse structures with various functionalities. As a proof of concept, the nanocomposites have been used for diagnosis and therapy applications. This study developed the synthesis protocols for multicomponent nanocomposites, and gave suggestions on how to design effective nanocomposites for biomedical applications.